2009
DOI: 10.1007/s11431-008-0352-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of short period InAs/GaSb superlattices on GaSb and GaAs substrates

Abstract: Type II superlattices (SLs) short period InAs(4ML)/GaSb(8ML) were grown by molecular-beam epitaxy on lattice-mismatched GaAs substrates and on GaSb substrates. A smooth GaSb epilayer was formed on GaAs substrates by inserting mulit-buffer layers including an interfacial misfit mode AlSb quantum dot layer and AlSb/GaSb superlattices smooth layer. SLs grown on GaAs substrates (GaAs-based SLs)showed well-resolved satellite peaks in XRD. GaSb-based SLs with better structural quality and smoother surface showed str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Deng et al [ 108 ] have also tried inserting a 1 ML of an InSb IF layer between InAs/GaSb T2SL grown on a Si substrate to attain a strain‐balanced condition. Jie et al [ 109 ] also studied the influence of inserting InSb IF layers at the SL interfaces grown on GaSb and GaAs substrates. Jie et al [ 113 ] also demonstrated growth of mixed‐like IFs (i.e., GaInAsSb‐like IFs) and found that the PL spectra of SL with mixed‐like IFs showed a stronger PL intensity and narrower full width at half maximum compared to InSb‐like IFs, however, the mixed‐like IFs appeared to be more sensitive to growth temperature than that with InSb‐like IFs as demonstrated by X‐ray diffraction (XRD) and atomic force microscope (AFM) measurements.…”
Section: Fundamental Materials Properties Of the Type‐ii Superlatticementioning
confidence: 99%
See 1 more Smart Citation
“…Deng et al [ 108 ] have also tried inserting a 1 ML of an InSb IF layer between InAs/GaSb T2SL grown on a Si substrate to attain a strain‐balanced condition. Jie et al [ 109 ] also studied the influence of inserting InSb IF layers at the SL interfaces grown on GaSb and GaAs substrates. Jie et al [ 113 ] also demonstrated growth of mixed‐like IFs (i.e., GaInAsSb‐like IFs) and found that the PL spectra of SL with mixed‐like IFs showed a stronger PL intensity and narrower full width at half maximum compared to InSb‐like IFs, however, the mixed‐like IFs appeared to be more sensitive to growth temperature than that with InSb‐like IFs as demonstrated by X‐ray diffraction (XRD) and atomic force microscope (AFM) measurements.…”
Section: Fundamental Materials Properties Of the Type‐ii Superlatticementioning
confidence: 99%
“…[103] The interfacial issue is the main obstacle for high-quality growth of InAs/GaSb T2SL which has a critical impact on the structural, optical, and device performance. Consequently, the intentional incorporations of interfacial layers are currently being employed to circumvent this challenge at the InAs/GaSb interfaces including GaAs-like, [104][105][106][107] InSb-like, [108][109][110][111][112] and ternary/ quaternary mixed-like IFs [113] with demonstrated evidence of enhanced device performance. Much evidence has proved that InAs/GaSb T2SL with GaAs-like IFs performs poorly for IR detection [104,105] and it is generally avoided.…”
Section: Materials Growth Of Inas/gasb and Inas/inassb T2slmentioning
confidence: 99%
“…With significant media attention focused on nanoscience and nanotechnology in recent years, materials science has been propelled to the forefront at many universities. Materials science encompasses various classes of materials, including electronic materials, functional ceramics, magnesium, material and processes for flat-panel displays, eco/environmental materials, sustainable energy materials, transportation materials, electronic packaging materials, etc.The field of electronic materials is of extraordinary importance to technology and society given the pervasiveness of electronic devices in day-to-day life [1][2][3][4][5][6][7][8][9][10][11]. Particular areas of interest focus on material science and technologies of relevace to silicon processing technologies and future scaling approaches.…”
mentioning
confidence: 99%
“…The field of electronic materials is of extraordinary importance to technology and society given the pervasiveness of electronic devices in day-to-day life [1][2][3][4][5][6][7][8][9][10][11]. Particular areas of interest focus on material science and technologies of relevace to silicon processing technologies and future scaling approaches.…”
mentioning
confidence: 99%